An Integrated Approach to Mandarin Processing: Food Safety and Nutritional Quality, Consumer Preference, and Nutrient Bioaccessibility. Issue 6 (23rd October 2017) - Putnik, Predrag; Barba, Francisco J.; Lorenzo, Jose Manuel; Gabrić, Domagoj; Shpigelman, Avi; Cravotto, Giancarlo; Bursać Kovačević, Danijela
Abstract: Mandarins are a member of the Citrus genus and are the focus of growing commercial interest, with satsuma mandarins ( Citrus unshiu ) and the common mandarin ( Citrus reticulata Blanco) being the most important mandarin varieties. The possible health benefits and functional properties of those fruits are often associated with the antioxidative function of vitamin C, carotenoids, and phenolic compounds. While most mandarins are consumed fresh, many are processed into juices (mostly cloudy), usually via thermal processing which can lead to the creation of off‐flavors and may diminish nutritional quality. The aim of this review is to summarize the most significant and recent information on the safety, sensorial properties, and nutritional benefits of mandarins and their processing into juice. The article also discusses recent information regarding the bioaccessibility of valuable, mandarin specific, compounds.